Stabilization of Flail Chest and Fractured Sternum by Minimally Invasive Repair of Pectus Excavatum - Murat Akkuş; Ayfer Utkusavaş; Murat Hanözü; Mehmet Kaya; Ihsan Bakir (The Thoracic & Cardiovascular Surgeon Reports, 2015)
Abstract We report a 55-year-old male patient with a massive flail chest that required chest stabilization by minimally invasive repair of pectus excavatum (MIRPE) employing a Nuss bar. Surgical stabilization of severe flail chest and fractured sternum with Nuss bar by MIRPE is a safe and useful treatment modality in properly selected patients.